Proposed Business Strategy for Sangun Laundry - Muhammad Satria Akbar Abbas; Mohamad Toha (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
With underutilized operational capacity. Sangun Laundry competes in the underserved laundry service market of Delatinos Residential Area, South Tangerang. A new business strategy that enlarges Sangun Laundry’s market share with current operational capacity is needed. To formulate one, the business environment is analyzed first. The external environment is examined using the PESTEL framework, Porter’s Five Forces, Cluster Analysis, and competitor analysis with data from literature reviews and customer survey. The internal environment is studied using Value Chain Analysis, Business Model Canvas, VRIO Analysis, and performance analysis with data from interview with the owner. The two environments are harmonized in SWOT analysis as the basis of strategy formulation, which uses Porter’s Generic Strategy, Diamond Strategy, and a new business model canvas. The result shows Sangun Laundry’s operational excellence and its need for improving customer service. Although Sangun Laundry excels in cost-efficiency and quality reputation by virtue of its resources and capabilities, underutilized operational capacity, lack of branding, and manual financial recording slow the business down. Low bargaining power of buyers, rising purchasing power, and high awareness of health hint higher future demand, but threats also come from tight rivalry, laundry appliance innovations, environmental disobedience, and quality mishaps. Sangun Laundry shall apply differentiation strategy where pick-up delivery and customer service become the value propositions, and serve the customer segment dominated by workers aged 36-55. A new customer service staff, who would operate a partner CRM software, is a required vehicle for customer service, which will boost brand perception and customer’s sharing intention.